2022
DOI: 10.3758/s13423-022-02193-y
|View full text |Cite
|
Sign up to set email alerts
|

Massive visual long-term memory is largely dependent on meaning

Abstract: Previous research demonstrated a massive capacity of visual long-term memory (VLTM) for meaningful images. However, the capacity and limits of a "pure" VLTM that is independent of conceptual information still need to be determined. In three experiments, participants memorized hundreds of images depicting real-world objects, along with visually similar images that were stripped of their semantic meaning. VLTM was evaluated using a four-alternativeforced-choice test including old and new images and their counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…This also agrees with results highlighted in Shoval et al. (2022) where they established that meaning is important for remembering massive amounts of visual information in adults and in Goujon et al. (2022) where they found that semantic information does enhance the encoding and maintaining of images in long‐term memory when assessed immediately (but not when assessed after weeks).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This also agrees with results highlighted in Shoval et al. (2022) where they established that meaning is important for remembering massive amounts of visual information in adults and in Goujon et al. (2022) where they found that semantic information does enhance the encoding and maintaining of images in long‐term memory when assessed immediately (but not when assessed after weeks).…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with the results outlined in Boucher et al (2016) where children's memory performance was better for concrete than for abstract pictures, marked by larger P600 repetition effects elicited by concrete compared to abstract designs and a more pronounced and localized recruitment of the left frontal region for concrete pictures. This also agrees with results highlighted in Shoval et al (2022) where they established that meaning is important for remembering massive amounts of visual information in adults and in Goujon et al (2022) where they found that semantic information does enhance the encoding and maintaining of images in long-term memory when assessed immediately (but not when assessed after weeks). Building on these findings, our comparative data on children and adults' performance additionally shows that the 'concrete-superiority effect' or the relative advantage conferred by meaningfulness is higher for children.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In other words, the testing effect appeared to selectively enhance the speed of retrieving conceptual information. Indeed, there is evidence that not just the testing effect but visual memory in general may be dependent on semantic content: although visual long-term memory can store thousands of everyday objects with a high degree of detail (Brady et al, 2008), visual long-term memory is quite poor for meaningless visual items encoded under similar conditions, i.e., one brief presentation per image (Shoval et al, 2022). On the other hand, other prior results argue against a semantic content-mediated theory.…”
Section: Discussionmentioning
confidence: 99%